An analysis of long-run relationship between ICT sectors and economic growth: evidence from ASEAN countries. (18th December 2019) - Chaiboonsri, Chukiat; Wannapan, Satawat; Cerulli, Giovanni
This paper is proposed to investigate the causal panel relationship between information and communication technologies (ICTs) segments and economic expansionary rates in ASEAN countries. Methodologically, the panel time-series data observed during 2006 to 2016 is employed to estimate the panel Granger causality test. According to the technical problem of lag selection for the panel causal analysis, the computationally statistical approach called Newton's optimisation method is helpfully applied to verify the suitable lag selection. The empirical results found that ICTs are not the major factor that causally motivates economic growth in ASEAN. This is confirmed by the extended section of the autoregressive distributed lag (ARDL) co-integration approach, which is based on Bayesian statistics combining with the simulation method called Markov chain Monte Carlo (MCMC). The results state Thailand is the only one among eight selected countries in ASEAN contained the long-run relationship between ICTs and GDP. This can be strongly concluded that the ICT sectors are not sustainable for driving economic growth in ASEAN. To address the issue, equitable educational systems and advanced infrastructural developments are the primary that should be corporately implemented.